Integrating Science and Politics for Public Health - Fafard, Patrick; Cassola, Adèle; de Leeuw, Evelyne (Palgrave Studies in Public Health Policy Research, 2022)
"This volume is a welcome and timely contribution to our understanding of public health policy making as an essentially political endeavour. A sophisticated mix of theoretical, conceptual and empirical analysis serves as a guide to the challenges inherent in making public policy that accounts for and improves population health." - Tom McIntosh, Professor of Politics and International Studies, University of Regina, Canada "The editors of this important book have assembled an impressive group of experts who understand the worlds of both public health, policy theory, and political science. They offer important insights into the challenges and opportunities of integrating these disciplines to the benefit of both." - Ilona Kickbusch, Professor and Founder of the Global Health Centre, Graduate Institute of International and Development Studies, Switzerland This open access book bridges the divide between political science and public health, whilst simultaneously embracing the complexities and differences of both. Although public health is inherently political, the tools and insights of political science are often ignored in public health scholarship. Bringing together academics and researchers working at the intersection of both, the book demonstrates how integrating these fields can help reconcile the roles of politics and scientific evidence in policymaking. It also highlights the key conceptual, methodological and substantive implications for bridging this divide, and charts a path forward for a movement towards political science with public health. Patrick Fafard is Professor at the Graduate School of Public and International Affairs, University of Ottawa, Canada. He is also Senior Investigator at the Global Strategy Lab, York University, Canada. Adèle Cassola is Research Director at the Global Strategy Lab, York University, Canada. Evelyne de Leeuw is Professor at the University of New South Wales, Australia, and Director of the Centre for Primary Health Care and Equity.